"É hoje que eu pego um peixão": brincadeiras, espaços, e frequência do brincar em uma instituição de acolhimento - CARVALHO, Milany Santos de (Universidade Federal do Oeste do Pará, 2023)
The objective of this work was to know how children in institutional care play in the Municipality of Santarém – Pará. The institutional welcoming space is considered an environment where different forms of child play take place, as well as a place where human development occurs. The participants were 05 children from five to twelve years old. As data’s instruments we opted for the socio-demographic data sheet, semi-structured individual interview script and observation scripts. Records of 5 minutes were made, totaling 300 minutes of systematic observation and 56 records of general observation of the institution. The results showed that 85% of the games occur in unstructured spaces, and 15% occur in structured spaces. Regarding the data obtained from general and systematic observations, it was revealed that symbolic play was the most frequent with 35, 85%, followed by construction play 28, 30%, physical exercise with, 21, 7%, turbulent with 7,5% and with rules, 3, 7%. A relationship was found between space and children’s play choices. In relation to the interviews, the children answered 15 questions about the routine and the playroom, evidencing in their speeches that they do not use the playroom as they would like, and even though they play in spaces that they would not like to play in the course of their daily lives. Therefore, this study contributes with empirical results on playing in a host institution, as well as elucidating the need for flexibility in the use of spaces for the occurrence of all forms of play. In addition, it is suggested that new policies be implemented in relation to the use of the toy library by all professionals in the institution, as well as the analysis and improvement of strategies that promote playing in the context of the institution.